Translation Methods and Procedures Found in the Harry Potter: the Chamber of Secrets Movie Subtitle - Clarence Usmany (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
While doing translation process several methods and procedures needed to be understood. This article focused on finding out the method and procedures proposed by Newmark (1988) done by the translator in order to tackle problems in translation.This article entitled “Translation Methods and Procedures Found in the Harry Potter: the Chamber of Secrets Movie Subtitle” were taking data randomly from two version of the movie subtitles “Harry Potter and The Chamber of Secrets.” The data taken were 5 phrases from each version of the subtitle that were collected with documentation methods. The data then analyzed by using descriptive qualitative method. The theory in this study used “A Textbook of Translation” written by Newmark (1988). Translation methods discovered are faithful translation, free translation, idiomatic translation, and communicative translation. Meanwhile, the procedure that were found are synonymy, cultural equivalent, functional equivalent, and modulation. The differences in both target and source language are sometimes philosophical hence making it beneficial to apply the correct methods and procedures. Moreover, not applying a correct methods and procedures can end up altered the actual meaning of the word and or not being able to find the closest equivalent meaning of the word. Therefore, a method and procedures all compiled by Newmark are the epicentrum of every translator in doing their job, the total awareness of each particular methods and procedures are expected to help translator to translates word without losing, altered, or shifting the correct contextual meaning.